Development and outlook of deep space communication network protocol - Jian-ping AN; Song JIN; Jun XU; Yu ZHANG; Li-wei SHAO (Tongxin xuebao)
The demand of developing deep space communication network was analyzed. Combining the characteristics of the deep space communication network, the deep space communication network architecture and transport protocols were summarized. Through introducing some key technology of the deep space communication network, the development di-rection of future deep space communication network is put forward and bright prospects are shown.